Collaborative Activities: Problematic Issues of Correlation Between National and International Law Norms - Kyrian, Iryna; Zhyhylii, Dariia (Problems of legality, 2026)
During the period of full-scale invasion, when open proceedings under Part 2 of Article 1111 of the Criminal Code of Ukraine are becoming more and more numerous, it is necessary to ensure the right to a fair trial (taking into account the norms of international humanitarian law and international human rights law) in criminal proceedings for the commission of crimes against the foundations of national security of Ukraine, which is the relevance of this study. The purpose of this scientific work is to conduct a detailed analysis of national and international legislation, their correlation, and the identification of conflicts and gaps. To achieve the goal of the study, the following methods were used: the method of analysis, which consisted in studying the current legislation of Ukraine, international humanitarian law and relevant judicial practice; the empirical method, which was used to collect and analyze statistical data on the application of Part 2 of Article 1111 of the Criminal Code of Ukraine in judicial practice, including surveys of specialists in the field of criminal justice, as well as the population that found themselves in temporarily occupied territories; comparative legal method of Ukrainian legislation and international humanitarian law. The results of the study revealed the issues of the correlation of national and international legislation. It was established that there is a gap in national law and issues in judicial practice. A survey of people from temporarily occupied territories was conducted, which helped to create public opinion on collaborative activities and legal awareness of the population. The survey of experts showed that in practice, national legislation does not clearly distinguish between the concepts of “cooperation with the enemy under duress” and “voluntary cooperation” (in the context of collaborative activities), as well as the presence of a conflict between the norms of national and international law (in the context of collaborative activities). It was revealed that due to the lack of a full interpretation of the norms and consistent judicial practice, similar cases are classified under different articles of the Criminal Code of Ukraine, which leads to violations of human rights, as well as to appeals to the European Court of Human Rights in the future.